STUDY OF THE GREEN COVER FULFILLMENT IN THE TOMB OF SULTAN SURIANSYAH TOURIST AREA ON THE RIVERBANK AREA OF THE KUIN - Dienny Redha Rahmani; Hanny Maria Caesarina (SINTA Journal (Science, Technology, and Agricultural), 2020)
Sultan Suriansyah tomb tourism area is a multi-role cultural heritage area classified in the religious, social and cultural aspects which is also a tourist attraction, economically it is an area that generates income for the residents because of the presence of tourists. Ecologically it has an important role as part of the city and supporting the Kuin riverbank. Therefore, it is necessary to study related to the fulfillment of green cover near the area to be able to assess the optimal functioning of this area both as a support for river banks and the function of the sustainable city of Banjarmasin. The green coverage was estimated by two methods, survey and Geographic Information System (GIS). The survey is an estimation of the canopy width formed on the condition of the trees. Estimation results show the average width of the canopy is around 5 meters that have not met good ecological criteria. The GIS result is still far from the minimum standard requirement. The difference in deficiency reaches ± 60% deficiency that has not yet reached the minimum green space requirement. A deeper study and revitalization of vegetation are needed for the sustainability of the Sultan Suriansyah tombs tourism area.